My indigo world : a true story of the color blue - Chang, Rosa Sung Ji (mineditionUS, 2023)
"Rosa, a Korean girl, falls in love with the color blue--the dazzling blue of the sea and sky, and the bold, bright indigo-blue stripe in her traditional hanbok robe. Years later, as an artist living in the United States, Rosa learns the ancient Korean method of indigo dyeing, creates indigo arts and crafts, and even grows her own indigo plants at a Baltimore community garden."--